Corrosion Behavior of Galvanized Steel Embedded in Concrete Exposed to Soil Type MH Contaminated With Chlorides - Baltazar-Zamora, Miguel Angel; Mendoza-Rangel, José Manuel; Croche, René; Gaona-Tiburcio, Citlalli; Hernández, Cindy; López, Luis; Olguín, Francisco; Almeraya-Calderón, Facundo (Frontiers in Materials, 2019)
This research evaluates the behaviour of corrosion in reinforced concrete, buried in a soil type MH, the present study represents the conditions of exposure that can find the foundations of infrastructure such as bridges, buildings, pavements, when in contact with a soil that could contain aggressive agents like chlorides and sulfates. In such concrete specimens a steel bar AISI 1018 and Galvanized Steel was embedded as reinforcement, the mixed concrete was of ratio w/c=0.45 (F´c = 350 kg/cm2), according to ACI 211.1, using two type cements CPC 30R (Type I) and CPC 30R RS (Type V). The corrosion rate was evaluated by electrochemical techniques, corrosion potential Ecorr (ASTM C-876-15) and Linear Polarization Resistance. LPR (ASTM-G59). These specimens of study were buried in a soil type MH contaminated with 0, 1, 2 and 3% NaCl as aggressive agent by weight of soil, the exposure time was 260 days where, the results show that when the presence of NaCl in the soil was increased to 2 and 3% the levels of corrosion are from high to very high in all concretes, presenting a little better performance the concretes reinforced with galvanized steel and a small benefit could be identified or related to the properties of a denser and less impermeable matrix that presented the concrete mix made with cement CPC 30R RS (Type V).